Optimalizing Learning Models and Srategy of Kitab Kuning at Bahrul Ulum Boarding School During Covid-19 Pandemic - Zulham Ainun Najib; Mohammad Saat Ibnu Waqfin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
According to the Big Indonesian Dictionary (KBBI), optimization comes from the word optimal which means best or highest. While optimization is a process of optimizing something or the process of making something the best. The learning model is a package or frame of the application of an approach, method and learning technique (Sudrajat, 2008). Kemp (Wina Senjaya, 2008) suggests that a learning strategy is a learning activity that teachers and students must do so that learning objectives can be achieved effectively and efficiently (Sudrajat, 2008). In December 2019, a new virus named Corona virus Disease 2019 appeared, which is usually abbreviated as Covid-19 in the Wuhan area, China. The spread of this virus is high, until March 2020 it entered Indonesia. The impact that occurs is the occurrence of chaos both from the economic, educational and other lines. In Islamic boarding schools, which initially studied the kitab kuning, now they have to use appropriate learning models and strategies so that learning is more optimal. The purpose of this study was to determine the models and strategies of learning the kitab kuning in Bahrul Ulum Islamic boarding school at the time of the covid-19 pandemic. The research method used is a qualitative method. Data were collected by interviewing informants in Bahrul Ulum Islamic boarding school Tambakberas Jombang. The results showed that the learning models used during the Covid-19 pandemic were Teacher Learning, Student Active Learning and Demonstrations. While the learning strategies are the Thinking Ability Improvement Learning Strategy (SPPKB), Expository Learning Strategy (SPE), and Project Based Learning. These models and strategies can be used because they are considered the most efficient to be used in learning during the Covid-19 epidemic.